Cytogenetic Analysis of Seven Species of Gekkonid and Phyllodactylid Geckos - Chrostek, Gabriela; Domaradzka, Aleksandra; Yurchenko, Alona; Kratochvíl, Lukáš; Mazzoleni, Sofia; Rovatsos, Michail (Genes, 2023)
Geckos (Gekkota), the species-rich clade of reptiles with more than 2200 currently recognized species, demonstrate a remarkable variability in diploid chromosome numbers (2n = 16-48) and mode of sex determination. However, only a small fraction of gekkotan species have been studied with cytogenetic methods. Here, we applied both conventional (karyotype reconstruction and C-banding) and molecular (fluorescence in situ hybridization with probes for rDNA loci and telomeric repeats) cytogenetic analyses in seven species of geckos, namely Blaesodactylus boivini, Chondrodactylus laevigatus, Gekko badenii, Gekko cf. lionotum, Hemidactylus sahgali, Homopholis wahlbergii (Gekkonidae) and Ptyodactylus togoensis (Phyllodactylidae), in order to provide further insights into the evolution of karyotypes in geckos. Our analysis revealed the presence of interstitial telomeric repeats in four species, but we were not able to conclude if they are remnants of previous chromosome rearrangements or were formed by an accumulation of telomeric-like satellite motifs. Even though sex chromosomes were previously identified in several species from the genera Hemidactylus and Gekko by cytogenetic and/or genomic methods, they were not detected by us in any examined species. Our examined species either have poorly differentiated sex chromosomes or, possibly, environmental sex determination. Future studies should explore the effect of temperature and conduct genome-wide analyses in order to identify the mode of sex determination in these species.
Keywords: celogenomová asociační studie; Gekkota; sex chromosomes; Sex Chromosomes; pohlavní chromozomy; ještěři; In Situ Hybridization, Fluorescence; zvířata; C-banding; karyotype; rDNA; hybridizace in situ fluorescenční; telomeres; Genome-Wide Association Study; heterochromatin; karyotypizace; Lizards; Animals; FISH; Karyotyping